Embedding of authentic assessment in work-integrated learning curriculum - Bosco, Anna; Ferns, Sonia (Asia-Pacific Journal of Cooperative Education, 2014)
Contemporary perspectives of higher education endorse a work integrated learning (WIL) approach to curriculum content, delivery and assessment. It is agreed that authenticity in learning relates to real-world experience, however, differentiating and strategically linking WIL provision and facilitation to assessment tasks and collation of authentic student evidence is critical. Irrespective of whether authentic learning tasks can be achieved in the education or workplace settings, the imperative of why an assessment is regarded as highly or minimally authentic needs to be better understood. The literature doesn't clearly describe such parameters for assessments, nor does comprehensive course review (CCR) use a structured framework to analyze WIL assessments in curriculum. An Authentic Assessment Framework (AAF) was designed to assist this gap in CCR and piloted at Curtin University to enable a consistent approach across programs and disciplines. This paper describes the process for developing that framework, highlighting the effectiveness in engaging WIL practitioners and informing authentic curriculum development.